Beliefs About Moral Obligation Structure Children's Social Category‐Based Expectations. Issue 1 (9th October 2018) - Chalik, Lisa; Dunham, Yarrow
Abstract : Young children view social category members as morally obligated toward one another, and expect these obligations to shape people's social behavior. The present work investigates how children specify which behaviors are constrained by social categories in this way. In two studies ( N  =   128), 4‐ and 5‐year‐old children predicted that morally positive behaviors would be directed toward in‐group members, and that morally negative behaviors would be directed toward out‐group members, but did not hold equally strong expectations about behaviors described as positive or negative for reasons irrelevant to morality. Thus, notions of morality are embedded within children's representations of social categories, such that when learning about novel moral norms, children immediately expect those obligations to uniquely hold within social groups.